Problems of the formation of a secondary linguistic personality in the context of linguocultural education - Abdurazakova Shahida Rahimovna (Peerian Journals Publishing, 2022)
The article is devoted to the issue of defining the concept of "linguistic personality". The conceptual content of a term is revealed by means of its constituent concepts: "linguistic personality" and "secondary linguistic personality". A formed linguistic personality is the result of any language education, and the result of education in the field of foreign languages is a secondary linguistic personality. It can be argued that a multicultural linguistic personality, formed in the process of teaching a foreign language, is an extension the qualities of a linguistic personality, that is, a linguistic personality within the framework of the native language, and the development of the qualities of a secondary linguistic personality within the framework of a foreign language
Keywords: Linguistics; secondary linguistic personality; communication; linguacultural education